Effect of a short, animated storytelling video on transphobia among US parents: randomized controlled trial - Amsalem, Doron; Greuel, Merlin; Liu, Shuyan; Martin, Andrés; Adam, Maya (JMIR public health and surveillance, 2025)
Background: Parents play a pivotal role in supporting transgender and gender diverse (TGD) children and adolescents. Yet only 35% of TGD youth describe their home as a gender-affirming place. Lack of parental support contributes to recent findings that TGD youth are approximately three times more likely to attempt suicide than their cisgender peers. In contrast, parents’ affirmation of their children’s gender identity significantly improves their mental health outcomes, by reducing anxiety, depression, and suicidality in this vulnerable population. Objective: Addressing the urgent need for effective, scalable interventions, this study evaluates a novel digital approach: short, animated storytelling (SAS) videos. We hypothesized that our 2.5min animated video intervention would reduce anti-trans stigma, or transphobia, and improve attitudes toward gender diverse children among US parents, by providing insight into the lived experiences of TGD youth. Methods: We recruited 1,267 US parents, through the Prolific Academic online research platform, and randomized them into SAS video intervention or control groups. We measured transphobia using the Transgender Stigma Scale (TSS), and attitudes towards transgender children using the Gender Thermometer, before and after watching the video. We compared outcomes between the two groups using 2X3 Analysis of Variance (ANOVA). Both groups were invited to return 30 days later to complete the measures again, before being offered post-trial access to the intervention video, which portrayed an authentic conversation between a mother and her transgender child. Results: Single exposure to a short, animated story video significantly reduced transphobia and improved attitudes towards transgender children among US parents, immediately post-intervention. We observed a significant group-by-time interaction in mean TSS scores (F(2,1)=3.7, p=.024) and significant between-group changes when comparing SAS video and control groups from baseline to post-intervention (F(1)=27.4, p<.001). Effect sizes (Cohen’s d) indicated small to moderate immediate changes in response to the 2.5min video, though the effect was no longer observed at the 30-day follow-up. Gender Thermometer scores revealed significant immediate improvements in the attitudes of participants in the SAS video intervention arm, and this improvement was sustained at the 30-day time point. Conclusions: Short, animated storytelling is a novel digital approach with the potential to boost parental support and affirmation of transgender children, by offering authentic insights into the lived experiences of TGD youth. Yet, repeated exposures to SAS interventions may be necessary to sustain these improvements over time. Future research directions could include developing and testing a series of SAS videos featuring the authentic lived experiences of several TGD youth. Evaluating the effect of such a series could meaningfully contribute to the fields of both digital health communication and transgender health. Digital approaches, like SAS videos, that support empathy and acceptance of TGD youth, could foster a more inclusive society in which every child can thrive. Clinical Trial: This study and its outcomes were registered on 01/24/2024 with AsPredicted.org (#159248), a clinical trial registry created in 2015 by the Wharton School at the University of Pennsylvania.
Gesehen am 08.09.2025